Simultaneous equation modeling of selected econometric variables on the Nigerian economy - Acha, C. K.; Uko, O. U. (Benin Journal of Statistics, 2019)
This study estimates various econometric variables to ascertain the two-way cause-and-effect relationship between Balance of Payment,Exchange Rate, and Inflation Rate in Nigeria. This aim was achieved by fitting an appropriate simultaneous equation model to Nigeria balance of payment and exchange rate. This study is limited to Nigeria Balance of Payment (BOP), exchange rate and inflation rate, which covers a period of 2001 to 2017. Based on the findings of this work, it is evident that relationships exist between exchange rate and BOP. It is clear that while exchange rate influences BOP negatively, the reverse is the case for Inflation Rate, since it influences exchange rate positively. It is therefore obvious that the outcome of this study will assist the Central Bank of Nigeria in monitoring the growth of Nigerian economy.